Energetics of karate (kata and kumite techniques) in top-level athletes - Doria, C.; Veicsteinas, A.; Limonta, E.; Maggioni, M. A.; Aschieri, P.; Eusebi, F.; Fanò, G.; Pietrangelo, T. (European Journal of Applied Physiology, 2009)
Breath-by-breath O2 uptake (VO2 VO2, L/min) and blood lactate concentration were measured before, during exercise, and recovery in six kata and six kumite karate Word Champions performing a simulated competition. [VO2maxmaximal anaerobic alactic, and lactic power were also assessed. The total energy cost ( VO2TOT , VO2TOTmL/kg above resting) of each simulated competition was calculated and subdivided into aerobic, lactic, and alactic fractions. Results showed that (a) no differences between kata and kumite groups in VO2max , VO2maxheight of vertical jump, and Wingate test were found; (b) VO2TOT VO2TOTwere 87.8 ± 6.6 and 82.3 ± 12.3 mL/kg in kata male and female with a performance time of 138 ± 4 and 158 ± 14 s, respectively; 189.0 ± 14.6 mL/kg in kumite male and 155.8 ± 38.4 mL/kg in kumite female with a predetermined performance time of 240 ± 0 and 180 ± 0 s, respectively; (c) the metabolic power was significantly higher in kumite than in kata athletes (p = 0.05 in both gender); (d) aerobic and anaerobic alactic sources, in percentage of the total, were significantly different between gender and disciplines (p < 0.05), while the lactic source was similar; (e) HR ranged between 174 and 187 b/min during simulated competition. In conclusion, kumite appears to require a much higher metabolic power than kata, being the energy source with the aerobic contribution predominant.